2020
DOI: 10.31124/advance.11533026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlates of loneliness in India: A systematic review

Abstract: Introduction:Loneliness is a critical psychosocial problem that affects mental health and wellbeing of the individuals and communities. This systematic review synthesized the current evidence on the prevalence and correlates of loneliness from empirical studies conducted in India. Methods:Adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, eight major databases and additional sources were searched. Studies were evaluated using following criteria: peer-reviewed j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(100 reference statements)
0
3
0
1
Order By: Relevance
“…In a survey conducted in 7 states of India, 9 increasing age, greater number of ADL requiring assistance, poor self‐reported health status and Alzheimer's disease (chronic condition) were identified as factors associated with social isolation. In a systematic review reporting on loneliness in India, 18 aging, educational attainment, source and level of income, family structure, marital status, religious practices, psychological attributes, comorbid conditions and group membership were identified as factors associated with loneliness. Similarly, it was found in a 3 year longitudinal survey that among older people participating in a hobby or sports or social activity group, future social isolation was significantly reduced 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey conducted in 7 states of India, 9 increasing age, greater number of ADL requiring assistance, poor self‐reported health status and Alzheimer's disease (chronic condition) were identified as factors associated with social isolation. In a systematic review reporting on loneliness in India, 18 aging, educational attainment, source and level of income, family structure, marital status, religious practices, psychological attributes, comorbid conditions and group membership were identified as factors associated with loneliness. Similarly, it was found in a 3 year longitudinal survey that among older people participating in a hobby or sports or social activity group, future social isolation was significantly reduced 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis reported prevalence of loneliness among older people to be 44% in India 18 ; and prevalence of social isolation in Building Knowledge Base on Population Ageing in India (BKPAI) survey was 19.7% (95% CI 19%–21%) 9 . Taking the prevalence to be 44% (to obtain higher sample size) and applying 5% absolute error, the minimum required sample size was rounded to be 400 with 95% confidence (CI).…”
Section: Methodsmentioning
confidence: 99%
“…Loneliness can be defined as the negative subjective feeling that results from a discrepancy between desired and actual social connections 2,3 . Estimates have shown that over 20% of older adults in the United States 4 , Eastern Europe 5 , India 6 , and six Latin American countries 7 reported feeling lonely. Due to the coronavirus disease 2019 (COVID- 19), predictions that stay-at-home recommendations and social restrictions would negatively affect a broad set of mental health indicators were expected, including a rise in loneliness 8,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Se incluyeron 5.108 participantes. La prevalencia global de la soledad en el periodo prepandémico fue del 33,1% (IC95%: 29,8), superior a la del periodo pandémico (ronda 1: 23,6%, IC95% : 20,6-26,9; ronda 2: 20,5%, IC95% : 17,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]5,ronda 3: 20,6;IC95%: 17,6). Sólo se evidenció una interacción significativa (p ≤ 0,05) entre la depresión y el tiempo; los participantes con depresión mostraron una mayor reducción de los niveles de soledad.…”
Section: Introductionunclassified